Compassion Fatigue Predicts Inadequate Pain Management: A Cross-Sectional Study of Iranian Nurses - Ghane, Golnar; Ahmadi, Yasamin; Chekeni, Amir Mohammad (PT. Nursing Genius Care, 2026)
Background: Compassion fatigue among nurses is a growing global concern that not only affects nurses' psychological well-being but may also compromise patient care quality, particularly pain management. However, the relationship between compassion fatigue and pain management practices remains underexplored.Objective: This study aimed to investigate the relationship between compassion fatigue and pain management practices among nurses, and identify predictors of inadequate pain management. Methods: A cross-sectional study was conducted with 412 nurses recruited from 10 teaching hospitals in Tehran, Iran using stratified random sampling. Data were collected using the Professional Quality of Life Scale (ProQOL) measuring compassion satisfaction, burnout, and secondary traumatic stress; and the Pain Management Practices Scale (PMPS). Data were analyzed using descriptive statistics, Pearson correlations, hierarchical regression, and structural equation modeling.. Results: High compassion fatigue was reported by 48.3% of nurses. Pain management practices were suboptimal (mean=58.64/100). Significant negative correlations were found between burnout and pain management (r=-0.512, p<0.001), and between secondary traumatic stress and pain management (r=-0.468, p<0.001). Regression analysis revealed that burnout (β=-0.324), secondary traumatic stress (β=-0.286), compassion satisfaction (β=0.298), nurse-to-patient ratio (β=-0.242), and work unit (β=-0.184) were significant predictors, explaining 51.6% of variance. Conclusion: Compassion fatigue significantly compromises nurses' ability to provide adequate pain management. Addressing this issue requires organizational interventions including psychological support, manageable workloads, and compassion-focused training to protect both nurse well-being and patient care quality.